Rules of Three Analysis in Persuasive Public Speaking Presentation - Yuli Angraini (English Department, University of Riau Kepulauan, Batam,Indonesia, 2016)
The objectives of this study were (1) to describe the effect of rules of three on persuasive public speaking presentation in speaking class and (2) to identify kinds of rules of three used by students in speaking class. The method of the study was descriptive study. Population of the study was all fourth semester students of Faculty of Teacher Training and Education in English Department in UNRIKA Kepulauan Riau Batam in Academic Year 2015/2016. The sample of this study was 24 students of fourth semester of Faculty of Teacher Training and Education in English Department in UNRIKA Kepulauan Riau Batam in Academic Year 2015/2016. The data was collected by using CD-RW form of presentation submitted by students. The data was analyzed and described by using Speech Evaluation Form which consisted of delivery of the speech and structure of the speech. It was identifiedthat only one group used rules of three in their group’s persuasive public speaking presentation and it made their speech more focus and understandable while other three groups ignored the rules of three in their persuasive public speaking presentation and it led to the message of the speech went nowhere as the audience caught many aspects inside it too broad. If rules of three used in persuasive public speaking, then it will bring them to success and possible for any of them who wants to be the next top-paid public speaker if they know how to use that technique during their speech ratherin the future. Keywords: rules of three, persuasive, public speaking presentation